Strategic Hedging Act: An Assessment of Indonesia's Decision to Join BRICS - Theresa Alicia Nahak; Rahel Jechire Kalisang (Andalas Journal of International Studies (AJIS), 2025)
Indonesia has always sought to maintain a neutral position in cooperating with Western countries, especially the United States, as well as with non-Western countries. However, on 6 January 2025, Indonesia took a surprising step by joining BRICS. BRICS is a multilateral institution aiming to reduce dependence on Western financial systems through the New Development Bank (NDB) and counter the dominance of the US dollar through the Local Currency Settlement (LCS) scheme. Indonesia’s entry into BRICS raises questions about the rationale behind such a move. Using Kuik and Goh's strategic hedging theory, which posits that small and medium economic powers maintain flexibility to navigate great-power pressure and uncertainty in order to protect themselves from risks and losses, this study employs qualitative research with a descriptive-analytical approach to examine the reasons behind Indonesia's decision to join BRICS. First, Indonesia joined BRICS as a form of economic pragmatism, driven by its current economic growth and China’s expanding influence in developing countries, positioning BRICS as a strategic opportunity for Indonesia’s prosperity. Second, Indonesia seeks to diversify its economy by fostering formal and informal ties with BRICS members and leveraging the NDB as an alternative financial institution to reduce reliance on Western-dominated systems. Third, BRICS membership is expected to elevate Indonesia’s global standing, enhance its bargaining power, and provide a platform to advance its national agenda in international decision-making processes.